2007
DOI: 10.1007/s10792-007-9096-z
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 expression in human irradiated uveal melanomas

Abstract: In contrast with studies showing an increase of COX-2 expression in other irradiated malignancies, irradiation was not a factor inducing COX-2 in uveal melanomas. Radiotherapy may, moreover, be a factor that reduces COX-2 expression in uveal melanomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
6
2
Order By: Relevance
“…These results are in contrast to the study of Ozdal et al (2008), which found a reduction of COX-2 expression in uveal melanomas after plaque radiotherapy.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results are in contrast to the study of Ozdal et al (2008), which found a reduction of COX-2 expression in uveal melanomas after plaque radiotherapy.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, there was no significant difference in COX-2 expression between photon-radiated and nonradiated uveal melanomas. These results are in contrast to the study of Ozdal et al (2008), which found a reduction of COX-2 expression in uveal melanomas after plaque radiotherapy.…”
Section: Discussioncontrasting
confidence: 99%
“…The COX-2 staining was shown only in 23/40 (57.5%), 52 2/15 (13.3%) 54 or 50/90 (55.6%). 55 Figueiredo et al 52 demonstrated a correlation of the COX-2 expression with the presence of epithelioid melanoma cells assessed according to Callender classification, which indicates higher cancer invasiveness, whereas no such relationships were found by Mougiakakos et al 55 The differences in evaluation of radiotherapy significance for changes in COX-2 levels in eye melanoma cells in papers 52,54,56 may be because of the effect of radiation on many processes, selection of cases for studies, but it is also likely that the choice of anti-COX-2 antibodies was important.…”
Section: Antibodiesmentioning
confidence: 99%
“…In studies of the COX‐2 expression in human eye melanomas, antibodies specific for fragments located at the C‐terminus of this protein were used . COX‐2 was detectable in almost all cases examined: 29/32 (90.6%), 42/42 (100%), and 17/18 (94.4%) .…”
Section: Possible Causes Of Different Cox‐2 Immunohistochemical Detecmentioning
confidence: 99%
“…In a recent issue of International Ophthalmology, Ozdal et al [1] wrote about cyclooxygenase-2 expression in human irradiated uveal melanomas. They reported that radiotherapy may actually decrease cycloxygenase-2 expression in uveal melanomas.…”
Section: To the Editormentioning
confidence: 99%